The Contribution Of Hand-Eye Coordination To Reaction Speedof Futsal Goalkeepersin The Bengkulu Provincial Club - Cikal Bakal Raka Siwi; Dwingki Marta Putra; Martiani Martiani (Journal of Multidisciplinary Research, 2026)
This study aims to examine the contribution of hand-eye coordination to the reaction speed of futsal goalkeepers in Bengkulu Province clubs. This study is a correlation study. The sample size was 15 people. The instruments used in this study were hand-eye coordination and smash accuracy tests. The results of the eye-hand coordination test showed a good contribution with an rtabel of 0.514 because the correlation coefficient between rxy = 0.96 > 0.514 and a contribution of 92.16%, which means that the contribution of eye-hand coordination to the reaction speed of futsal goalkeepers in Bengkulu Province clubs is significant and large. Thus, the hypothesis stating that “there is a strong contribution between hand-eye coordination and the reaction speed of futsal goalkeepers in Bengkulu Province clubs” is accepted. This means that there is a contribution of hand-eye coordination to the reaction speed of futsal goalkeepers in Bengkulu Province clubs.